Mangrove Restoration Using Rubberwood Fly Ash to Produce Biodegradable Seedling Pots for Coastal Erosion Control - Siriphat Sirikunpitak; Kuaanan Techato; Payom Rattanamanee; Apichat Choomkong; Khamphe Phoungthong (BioResources)
The increasing amount of fly ash from daily energy combustion, coupled with land use changes from mangrove forests, has led to an increase in severe coastal erosion. This study aims to utilize fly ash by adding value to biodegradable nursery pots, which can manage fly ash and reduce the use of seedling bags. The pots also have indirect benefits in preventing coastal erosion. The seedling pots are made from rubberwood fly ash (RWFA), clay, and sand. The composition of RWFA is analyzed using X-ray diffraction and fluorescence spectroscopy. The total concentration of a specific contaminant in a waste or soil sample is measured using the total threshold limit concentration (TTLC). Hydrodynamic simulations are conducted to optimize the layout of the pots to reduce the wave velocity. This study determined that RWFA, which is composed of 38.9% CaO, 11.3% SiO2, 8.9% organic matter, 8.8% total K2O, 1.0% total P2O5, and 0.006% total N, can be used as an ingredient in pots and plant nutrients. Moreover, the seedling pot design can reduce the speed of the water velocity by placing it in a suitable position. Furthermore, the TTLC value of the pot does not exceed the standard value.